Handgrip and functional mobility in elderly with different levels of physical activity - Dayane de Oliveira Macedo; Letícia Mendes de Freitas; Marcos Eduardo Scheicher (Universidade de São Paulo, 2014)
The proportion of elderly people is growing worldwide and, with this, there is an increase of chronic-degenerative conditions such as impaired balance and falls. The physically active elderly tends to an improved response in muscle strength, flexibility and postural balance. The present study aimed to evaluate and compare the grip strength and mobility of elderly people with different levels of physical activity. The sample consisted of 44 elderly with 60 years or more, both sexes, divided in: 18 elderly practicing volleyball adapted (AVG), 13 elderly practicing some physical activity (AG) and 13 sedentary elderly (SG). Grip strength was assessed by a hydraulic dynamometer and mobility through the test "Timed Up and Go" (TUG). Data were evaluated using the Kolmogorov-Smirnov test, to check normality. The comparison of the results of the three groups was performed by ANOVA with Tukey post-test, with p<0.05. The results showed that grip strength (p=0.008) and mobility (p=0.003) were better to AVG when compared to the other groups. It is suggested that the sports practice implement the gains in functional mobility and strength when compared to purely non-specific exercise and inactivity.